2021
DOI: 10.1039/d0qi01259a
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering of NiCo-layered double hydroxide hollow nanocages for highly selective photoreduction of CO2 to CH4 with suppressing H2 evolution

Abstract: We found that abundant defects could be created in the HC-NiCo-LDH by constructing a hollow nanocage morphology. The HC-NiCo-LDH showed excellent CO2 photoreduction performance that increasing the CH4 selectivity while suppressing the H2 evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…In addition, the addition of alkaline Co cations further increases the CO 2 adsorption capacity of the material and suppresses the generation of H 2 by-products. [43,46] This further confirms the effectiveness of the Ni 7 Co 3 -GR material in photocatalytic CO 2 reduction.…”
Section: Photocatalytic Co 2 Reduction Performancesupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, the addition of alkaline Co cations further increases the CO 2 adsorption capacity of the material and suppresses the generation of H 2 by-products. [43,46] This further confirms the effectiveness of the Ni 7 Co 3 -GR material in photocatalytic CO 2 reduction.…”
Section: Photocatalytic Co 2 Reduction Performancesupporting
confidence: 65%
“…In addition, active H* coupling inevitably occurs to form a small amount of H 2 molecules. [43][44][45] Using the Ni 7 Co 3 -GR catalyst leads to superior CO photocatalytic yield and high selectivity during the catalytic process because electron-rich Co facilitates the generation of a large number of electrons, separation of carrier, and adsorption of visible light. In addition, the addition of alkaline Co cations further increases the CO 2 adsorption capacity of the material and suppresses the generation of H 2 by-products.…”
Section: Photocatalytic Co 2 Reduction Performancementioning
confidence: 99%
“…The spectral g values for Ni 2+ ions are usually in the range 2.2–2.3, as shown in previous reports. 30 Fig. 3f shows that HD-CoNi-LDH produced a strong signal at g = 2.21, close to the g value of the superexchange coupled pair Ni( ii )–O–Ni( ii ) ( g = 2.25); 31 this indicated that many defects were present, mainly in the Ni site, and there were more Ni( ii )–O–Ni( ii ) defects in Ni( ii )-HD-CoNi-LDH than in Ni( ii )-bulk-CoNi-LDH.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the high-concentration alkaline solution used in the synthesis process requires a large amount of water for washing, resulting in excessive waste of water resources. 80,81 In view of this, Song et al successfully designed a green atom-economic method for various LDHs preparation, such as MgAl-LDHs and MgFeAl-LDHs, etc. 82 Taking MgAl-LDHs as an example, an aqueous solution containing Mg(OH) 2 and Al(OH) 3 was added with carbonic acid solution under vigorous stirring, and the resulting mixture was aged at 80 1C for 2 days to obtain the pure product without washing.…”
Section: Pristine Ldhsmentioning
confidence: 99%